Framing responsibility for depression: how U.S. news media attribute causal and problem-solving responsibilities when covering a major public health problem. Issue 2 (2nd April 2016) - Zhang, Yuan; Jin, Yan; Stewart, Sean; Porter, Jeannette
ABSTRACT: This paper analyzes how major U.S. print and broadcast news media framed depression causal and problem-solving responsibilities at individual and societal levels over the past three decades. Results from the content analysis showed that the media placed more causal and problem-solving responsibilities on individuals than the society. However, references to societal solutions increased moderately over time. Organizational differences emerged in news attribution of responsibilities, as print media presented more individual-level causes while broadcast media focused more on solutions at both individual and societal levels. Additionally, local newspapers put more problem-solving responsibilities on individuals than national newspapers, while a cable news channel allocated more time to the discussion of overall depression responsibilities than network TV. Findings are discussed in the context of cultural orientations, organizational constraints, changing practice and trends in health news reporting, and the broader political/social environment in which the news media operate. Practical implications for health journalism, mental health communication and advocacy, and public health policy-making are discussed.